Pilgrimage Tourism: A Study of Amritsar City - Kaur, Manpreet; Pannu, Jaspreet; Noonwal, Vijender (International Journal of Advanced Research in Peace, Harmony and Education; Vol 7 No 2 (2022): International Journal of Advanced Research in Peace, Harmony & Education, 2022)
Tourism is a strategy for the development of any nation which becomes elite platform for the economic achievements. The custom of pilgrimage in Amritsar is highly animus and numeral of localities having religious concern is so wide that the whole Amritsar may actually be regarded as single and magnificent sustained holy space. It has widely contributed to the foreign exchange and provides employment opportunities to all sectors of economy. Every year around 7 million pilgrims visit the shrines which have contributed effectively to the growth and development of the places. Furthermore, this research is providing the informative collection of data regarding the ample perspectives of pilgrimage tourism in Amritsar. How to cite this article: Kaur M, Pannu J, Noonwal V. Pilgrimage Tourism: A Study of Amritsar City. Int J Adv Res Peace Harm Edu 2022; 7(2): 1-5. DOI: https://doi.org/ 10.24321/2455.9326.202201